Investigation of Optical Ionization of Strontium via 5s21S0 ⟶ 5s5p 3<svg xmlns:xlink="http://www.w3.org/1999/xlink" xmlns="http://www.w3.org/2000/svg" style="vertical-align:-5.0608pt" id="M1" height="19.3125pt" version="1.1" viewBox="-0.0657574 -14.2517 16.5992 19.3125" width="16.5992pt"><g transform="matrix(.017,0,0,-0.017,0,0)"><path id="g190-81" d="M46 650V622C120 617 128 613 128 525V125C128 42 120 34 40 28V0H311V28C221 34 212 39 212 124V281L286 262C297 261 316 261 331 263C429 275 526 338 526 468C526 533 501 579 462 609C422 638 364 650 293 650H46ZM212 559C212 588 215 600 223 606C230 613 251 618 279 618C361 618 430 572 430 464C430 337 350 302 285 302C252 302 225 309 212 314V559Z"/></g><g transform="matrix(.012,0,0,-0.012,9.697,-7.578)"><path id="g54-73" d="M339 262C339 340 273 403 193 403S48 340 48 262S113 121 193 121S339 184 339 262ZM283 262C283 210 242 168 193 168S104 210 104 262S144 356 193 356S283 314 283 262Z"/></g><g transform="matrix(.012,0,0,-0.012,9.697,4.995)"><path id="g22-47" d="M415 0V41C335 46 327 62 327 127V635C236 611 161 593 93 583V547L150 544C187 541 192 535 192 483V127C192 59 182 46 102 41V0H415Z"/></g> ⟶ 5s5d 3D2 ⟶ 4dnp (or 4ndf, n = 39) for Isotope Selectivity Enhancement - Cheon, Donguk; Iwata, Yoshihiro; Miyabe, Masabumi; Wakaida, Ikuo; Hasegawa, Shuichi (Journal of Spectroscopy, 2018)
We investigated a promising three-step resonance ionization scheme of strontium (Sr) 5s2 1S0 ⟶ 5s5p 3P1° ⟶ 5s5d 3D2 ⟶ 4dnp (or 4dnf, n = 39) using the first-step intercombination transition for the enhancement of isotope selectivity. The power broadening observed in the 2nd transition indicates that laser power of less than 0.2 mW is sufficient for saturating this transition. Isotope separation can be successfully expected with application of the 3rd transition due to the narrow width of the 4dnp (or 4dnf, n = 39) autoionization level, paving the way for analysis of trace 90Sr in environmental applications.